(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the concept of labor management, features, functions, social nature and types of labor management are mentioned in this article. In addition, the types and methods of labor management are explained. Levels of labor management are highlighted. The Republic of Uzbekistan has been a member of the International Labor Organization since 1992, and until today, 14 conventions of this Organization have been ratified.